Trends, cost and challenges of oil and gas technology - Hein, Htet Zaw (2018)
The oil & gas market is very important globally. Mainly, overall trends and cost oil and gas technology are focused in this project and also challenges in this industry. The priority of this project is about the trend of modern technology and their roles and importance in oil and gas industry. The findings on this report are mostly on internet research and publish paper on internet. The main purpose of this project is to do research on challenges of oil and gas technology since from last decades until today. The 1st part of this research introduces the methodology of oil and gas industry and technology changes in oil and gas industry. This research is looking into the challenges and the trends of technology in oil and gas industry while technology become advance according to the time. Therefore, this project also forecast oil prices by using formula. Moreover, this research identifies the impact of other technology on oil and gas industry in past time and also the trend of the technology that can make changes and positive impact on this industry. Lastly, this project mentioned the importance of other alternative energy sources and their technology because these alternative resources can be applied efficiently and environmentally. The author expects to give a better understanding on the trend of technologies in oil and gas industry. This report will highlight to understand about the cost, trends and challenges of the oil and gas technologies.